2021
DOI: 10.1108/ijchm-10-2020-1177
|View full text |Cite
|
Sign up to set email alerts
|

Customer experience and brand loyalty in the full-service hotel sector: the role of brand affect

Abstract: Purpose This study aims to propose a comprehensive causal model to examine the relationships between customer experience and four key factors in brand building, i.e., brand loyalty, brand trust, brand affect and brand involvement. The dimensionality of customer experience in full-service hotel is also particularly examined in relation to brand building. Design/methodology/approach Three steps of data collection were used: interviews of 50 customers on their experiences of staying full-service hotels, a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
2
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 91 publications
6
43
2
2
Order By: Relevance
“…CCE is the customer experience resulting from the co-creation activity. Guan et al (2021) investigated the relationship between customer experience and BT and found that experience is related to trust, which is consistent with the findings of Ha and Perks (2005) and Walter et al (2013) . Kamboj et al (2018) found that customer participation, which is related to CCE, positively impacts BT.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 83%
See 1 more Smart Citation
“…CCE is the customer experience resulting from the co-creation activity. Guan et al (2021) investigated the relationship between customer experience and BT and found that experience is related to trust, which is consistent with the findings of Ha and Perks (2005) and Walter et al (2013) . Kamboj et al (2018) found that customer participation, which is related to CCE, positively impacts BT.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 83%
“…Several scholars have investigated the relationship between customer experience and BT ( Ha and Perks, 2005 ; Walter et al, 2013 ; Guan et al, 2021 ); however, they have largely overlooked the relationship between CCE and BT even though both concepts are fundamental in measuring consumer behavior.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…CBE (Kumar et al , 2019; Le et al , 2021), which is reflected by purchase, referral, influence and customer knowledge (Kumar and Pansari, 2016). The literature review (Appendix 2) has demonstrated that various brand strategies, including quality and equity (Liu et al , 2017; Yang and Lau, 2015), emotions, aesthetic perception, authenticity (Choi and Kandampully, 2019; Kim et al , 2020), brand experience as well as luxury value (Ahn and Back, 2018; Guan et al , 2021), have been adopted to investigate particular aspects of customer engagement.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In addition, luxury hotel brand strategies aim at building, developing and consolidating the association between brands and consumers (Guan et al , 2021; Le et al , 2021). It is suggested that when a luxury hotel brand successfully establishes a solid, two-way connection with its customers, that brand can then fully harvest customer values (Garmaroudi et al , 2021; Zhang et al , 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Loyalty has been stressed by several authors as being one of the most important factors which determine the success of a company Kartika et al, 2020;Latif et al, 2021;Anser et al, 2021;Guan et al, 2021). In terms of these findings, it is important for a company to be able to instill loyalty in its consumers' minds in a consistent manner, in order to prevent them from buying products from competitors.…”
Section: Introductionmentioning
confidence: 99%